Persepsi Petugas Puskesmas terhadap Pelaksanaan Vaksinasi Covid-19 pada Era New Normal - sudiman, dina (Jurnal Inspirasi, 2021)
This study aims to determine the perceptions of health center staff on the implementation of Covid-19 vaccination in the new normal era in their willingness to vaccinate Covid-19. The qualitative descriptive method was carried out by distributing questionnaires using google forms to 38 puskesmas officers, who were selected as informants because they were the priority targets for Covid-19 vaccination recipients. The results of this study stated that the perceptions of public health center officers on the implementation of Covid-19 vaccination in the new normal era showed that based on perceptions of successful vaccination, 61.5% agreed that Covid-19 vaccination could reduce mortality and 63.2% strongly agreed that their status as officers puskesmas makes it easy to get vaccinated. The results of this study stated that the perceptions of public health center officers on the implementation of Covid-19 vaccination in the new normal era showed that based on perceptions of successful vaccination, 61.5% agreed that Covid-19 vaccination could reduce mortality and 63.2% strongly agreed that their status as officers puskesmas makes it easy to get vaccinated. By considering the implementation of vaccination and recording reporting, 100% of officers stated that they were willing to vaccinate Covid-19. A good understanding of AEFI (Post-immunization Incidence) will be able to positively contribute to acceptance of the willingness to vaccinate, so that even though the concern about AEFI reaches 64%, the willingness to vaccinate is 100% willing. Further research is needed to assess the relationship between the criteria for implementing Covid-19 vaccination and the willingness to vaccinate Covid-19.